2020
DOI: 10.1080/13621718.2020.1730546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transverse magnetic field on weld formation and microstructure & properties of high-speed hot-wire tungsten inert gas welding joints

Abstract: A transverse magnetic field generator combined with high-speed hot-wire tungsten inert gas welding system is used to generate an external magnetic force to adjust the molten pool behaviours and the arc. Owing to the forward external magnetic force is helpful to balance the backward arc shear stress and the stirring of the electromagnetic force on molten pool, the weld formation and joint microstructure are improved, and the corrosion resistance of the joint is increased. The test results show that only a low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Tungsten inert gas welding is very suitable for studying the deflection behavior of arc under magnetic field because of its unique characteristics that only arc exists. Zhao et al [ 79 ] adopted an TMF in high‐speed hot‐wire TIG welding to adjust the flow of molten pool and the weld bead. Since the electrode direction is opposite to that in Figure 2c, the arc receives an electromagnetic force in the welding direction.…”
Section: Effect Of Magnetic Field On the Arc Weldingmentioning
confidence: 99%
“…Tungsten inert gas welding is very suitable for studying the deflection behavior of arc under magnetic field because of its unique characteristics that only arc exists. Zhao et al [ 79 ] adopted an TMF in high‐speed hot‐wire TIG welding to adjust the flow of molten pool and the weld bead. Since the electrode direction is opposite to that in Figure 2c, the arc receives an electromagnetic force in the welding direction.…”
Section: Effect Of Magnetic Field On the Arc Weldingmentioning
confidence: 99%
“…Schneider et al [10] found that porosity defects in the aluminium alloy were decreased obviously when the frequency and intensity of the alternating magnetic field were sufficient. Besides, influencing mechanism of magnetic field on welding has been studied by some scholars [11, 12]. The keyhole stability and energy distribution in molten pool could be changed by magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Voigt et al 31 constructed an induction coil of a new kind to preheat the filler wire and demonstrated stable arc to join mild steel plates. Zhao et al 32 demonstrated a method to avoid arc blow by introducing a magnetic field in transverse direction during welding of ferromagnetic Q235 steels.…”
Section: Introductionmentioning
confidence: 99%